Efficient Punishment for Insider Trader in Merger: Interjected Values of Economic Analysis of Law - Sugianto, Fajar; Tokuyama, Shintaro (University of Jember, 2024)
Corporate crime is one of the crimes that arise with the advancement of economic, technological, and trade liberalization activities. The problems with handling non-conventional crimes are due to the difficulty in determining the victims and criminal prosecution of perpetrators. Corporate liability and imposing sanctions on corporate entities are still strongly influenced by the societas delinquere non potest principle. One of the capital market crimes that may occur as a corporate crime is insider trading, which can be defined as securities trading transactions conducted by insiders utilizing insider information that has not been published. Information on a merger, a form of corporate restructuring, is categorized as material facts. When insider trading occurs in the merger process, verifying it for punishment is complicated considering the legal vacuum to convict such a crime. While closely related to financial matters, the prosecution of corporations also intersects with purposes and functions that protect society and individual offenders. Economic analysis of the law can answer the legal vacuum and determine the important aspects of proper legal practice, so that a specific and appropriate punishment can be found for the offense, considering that not all penalties can be imposed on corporations.KEYWORDS: Economic analysis of law, Punishment, Insider trading, Merger.